2018
DOI: 10.1186/s42269-018-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

A renoprotective role of chitosan against lithium-induced renal toxicity in rats

Abstract: Background: Lithium (Li) is considered as the first therapeutic line for treatment of bipolar affective disorders and manic-depressive illness. Renal toxicity can be categorized as the most common undesirable side effect of Li therapy. Therefore, the present study aimed to reveal efficiency of chitosan (CS) as a natural chelator against renal toxicity induced as a result of Li injection. During current experiment, the renal functions (urea, creatinine, blood urea nitrogen (BUN), uric acid and total protein) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 71 publications
(75 reference statements)
1
11
0
Order By: Relevance
“…Chitosan and maitake nanostructures have great capability to sharpen the antifree radical system through the elevation of GSH and catalase levels. These results complied with Aboulthana and Ibrahim, 41 who exemplified the reno-protective influence of chitosan towards renal impairment induced by lithium. Further, agreed with literature, 42 Santos et al previously indicated that the evacuation of oxidative free radicals, particularly the hydroxyl radicals driven to eminent advancement in renal function of cisplatin-induced renal toxicity rats.…”
Section: Discussionsupporting
confidence: 89%
“…Chitosan and maitake nanostructures have great capability to sharpen the antifree radical system through the elevation of GSH and catalase levels. These results complied with Aboulthana and Ibrahim, 41 who exemplified the reno-protective influence of chitosan towards renal impairment induced by lithium. Further, agreed with literature, 42 Santos et al previously indicated that the evacuation of oxidative free radicals, particularly the hydroxyl radicals driven to eminent advancement in renal function of cisplatin-induced renal toxicity rats.…”
Section: Discussionsupporting
confidence: 89%
“…Shaterpour et al [55] reported that focal moderate lymphocytic infiltrations were observed in the interstitial area in the renal tissue of the group administered LIT. Again, Aboulthanae and Ibrahim [56] detected tubular degeneration in the kidney cortex and vacuolization in the endothelial cells lining the glomerular clusters in the LIT-treated group. In the present study, it was observed that the normal structure was preserved in the renal cortex and medulla of the CNT, SIL, Vit C, and SIL+Vit C groups, and no histopathological changes were observed.…”
Section: Discussionmentioning
confidence: 93%
“…After three weeks animals were sacrificed, brain was removed and the cerebellum was separated from the rest of the brain and fixed in formaldehyde 8 for 24 hours.…”
Section: Methodsmentioning
confidence: 99%